2010
DOI: 10.1590/s1517-83822010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated extracellular NH4+ affects the motile chemosensory responses of batch-cultured Oxyrrhis marina

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…O. marina can also use extracellular ammonium as a feeding cue, but this can be highly context-dependent. 60 When O. marina cells were prey-saturated or less motile due to recent prey consumption, they were less likely to track towards extracellular ammonium. Chronic exposure to high concentrations of ammonium can also impair chemotaxis towards ammonium.…”
Section: Prey Capture and Predator Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…O. marina can also use extracellular ammonium as a feeding cue, but this can be highly context-dependent. 60 When O. marina cells were prey-saturated or less motile due to recent prey consumption, they were less likely to track towards extracellular ammonium. Chronic exposure to high concentrations of ammonium can also impair chemotaxis towards ammonium.…”
Section: Prey Capture and Predator Avoidancementioning
confidence: 99%
“…These data suggest a ''window of opportunity'' when conditions are most favorable to detect positive prey tracking by O. marina. 60 Predators use chemical cues to capture and subdue their prey. For example, karlotoxins-1 (15) and -2 ( 16) produced by Karlodinium veneficum can cause prey to become immobilized prior to ingestion by K. veneficum.…”
Section: Prey Capture and Predator Avoidancementioning
confidence: 99%
“…2020c). Moreover, excreted ammonia is also demonstrated to elicit positive chemotaxis (Stocker and Seymour 2012) in gametes of Chlamydomonas allensworthii (Govorunova and Sineshchekov 2005) and in Oxyrrhis marina (Martel 2010). Various extracellular metabolites such as short‐peptides (Brown et al.…”
mentioning
confidence: 99%
“…As a by-product of feeding, predators excrete ammonia which is a preferred source of nitrogen for many microalgal species and is reported to alter the photosynthetic properties of microalgae such as Dunaliella tertiolecta (Fabregas et al 1989, Deore et al 2020c). Moreover, excreted ammonia is also demonstrated to elicit positive chemotaxis (Stocker and Seymour 2012) in gametes of Chlamydomonas allensworthii (Govorunova and Sineshchekov 2005) and in Oxyrrhis marina (Martel 2010). Various extracellular metabolites such as short-peptides (Brown et al 2019), free amino acids (Gill and Poulet 1988), fatty acids (Tambiev et al 1989), lipids (Kind et al 2012), alkaloids (Volk et al 2009), aldehydes (Ribalet et al 2007), and indole derivatives (Doan et al 2000) are reported to act as chemical cues in prey searching, attraction, detection, recognition, and predator deterrence process (Mendes and Vermelho 2013).…”
mentioning
confidence: 99%